LIFELONG LEARNING E O DESENVOLVIMENTO DE SOFT SKILLS: UM ESTUDO DA APLICAÇÃO DESTES CONCEITOS NO ENSINO SUPERIOR - Canfield, George de Salles (2021)
This study analyzes the applicability of Lifelong Learning concept, in the teaching environment, as a way of adapting future needs and knowledge by developing Soft Skills, the so-called human and social skills. First, the concept of Lifelong Learning and its relationship with the student's personal and professional development are studied. Second, the correlation of Soft Skills are analyzed with students' interpersonal skills. This qualitative research is a case study about the creation and implementation of the Digital Business discipline and its students' perception. As result, there is a strong link of interpersonal skills development with the students' goals and needs in relation to their personal and professional future, highlighting the feedback movement from both concepts, as boosting human skills as building a meaningful learning path for life.